Clinical Learning Models in Nursing Students and Their Impact on Work Readiness - Al-Bahra, Al-Bahra; Darmojo, Hardjito S; Purnomo, Andri Cahyo; Suciana, Ewin (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
The clinical learning model is a crucial component of nursing education because it plays a direct role in shaping students' competencies and work readiness. Work readiness is a key indicator of the success of the educational process, particularly in facing the complex and dynamic demands of professional nursing practice. This study aims to analyze the influence of the clinical learning model on nursing students' work readiness. The study used a quantitative design with a descriptive analytical approach. The study sample consisted of 100 final-year nursing students who had participated in clinical practice, selected using a purposive sampling technique. Data were collected using a structured questionnaire that measured students' perceptions of the clinical learning model and their level of work readiness, which included aspects of clinical competence, self-confidence, communication, and professional readiness. Data were analyzed through univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using logistic regression. The results showed that most respondents rated the clinical learning model as good and had a high level of work readiness. Bivariate analysis showed a significant relationship between the clinical learning model and students' work readiness (p < 0.05). Multivariate analysis revealed that the clinical learning model was the dominant factor influencing nursing students' work readiness after controlling for age, gender, and length of clinical practice. This study concludes that implementing an effective and structured clinical learning model can improve nursing students' work readiness. Therefore, strengthening clinical learning strategies needs to be a priority in nursing education curriculum development.